Lanthanide Geochemistry and Fluid Inclusion Peculiarities of the Fluorite from the Barite Deposits South of Kresevo (Bosnia and Herzegovina) - Ladislav A. Palinkaš; Ivan Jurković (Geologia Croatica, 2010)
Strata-bound barite deposits occur in Devonian dolomites, situated in the Mid-Bosnian Palaeozoic Schist Mountains. These contain barite as the main ore mineral (5.9 wt% SrSO4 on average and d34S= +8.3‰) which comprises 90-99 wt% of the bulk ores. The subordinate components are calcite, fluorite, Hg-Sb-tetrahedrite, pyrite and quartz. Analysis of REE by INAA revealed an extremely low content of lanthanides (1.584 ppm), negative Eu anomalies (Eu3+/Eu+ = 0.7398), and (Tb)N/(La)N = 6.2 indicating late-stage mineralization. Primary fluid inclusions show a uniform number of infilling phases (L+V+S), and persistent volume ratio. This indicates homogeneity of the hydrothermal ore-forming fluids and an absence of boiling phenomena at the time of fluorite formation. Th is between 200° and 310°C, with a distinctive maximum at 250°C. Tfm -20.3°C predominates but careful examinations of the early melting behaviour of the inclusions warrants the existence of Tfm -51°C, and the presence of CaCl2. High salinity between 25 and 26 wt% eq. NaCl was determined from the hydrohalite melting temperature (Tmh). Some additional daughter minerals are also present. Fluorite, barite and calcite formed from the high saline waters probably originated by mixing of heated hydrothermal fluids with the highly evolved post-Variscan Upper Permian formation waters. This is supported by the study of the isotopic composition of the carbon, oxygen and sulphur of the paragenetic carbonates and sulphides.